Intercalary diaphysometafisary humeral reconstruction with nonvascularized peroneal graft and external fixation - Yulay Enrique Hernández-Rojas; Héctor Gabriel Díaz-Carrillo; Esteban Hernández-Ruiz (Revista Electrónica Dr. Zoilo E. Marinello Vidaurreta, 2023)
For the reconstruction of bone defects, after marginal intercalary resection caused by excision of benign or malignant tumors of low intensity, various surgical techniques have been proposed. Intercalary bone reconstruction with nonvascularized peroneal autologous graft is one of the most recommended. Two pediatric patients, one male and one female, with multicameral solitary cyst and osteochondroma, respectively, are presented. The humoral examinations were normal. Radiographic studies showed characteristic features of these lesions: irregular rounded images, alternating radiotransparent and radiodense, sclerosis of their cortical edges thinned intact. They underwent surgical interventions for humeral reconstruction intercalary with nonvascularized peroneal graft. To stabilize the graft, external fixation with transfixiating metal pins coupled to a rigid metal frame was used. The post-operative phase went smoothly with rigorous follow-up to bone remodeling and complete rehabilitation for nine months after surgery.